2019
DOI: 10.1176/appi.ajp.2018.18091075
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Sequentially Adding Cognitive-Behavioral Therapy or Antidepressant Medication for Adults With Nonremitting Depression

Abstract: Background Adults with major depressive disorder (MDD) frequently fail to achieve remission with an initial treatment. The sequential addition of psychotherapy after failure to remit with an antidepressant medication can target residual symptoms and protect against recurrence, but the utility of adding antidepressant medication after non-remission with cognitive behavior therapy (CBT) has received little study. Method Previously untreated adults with MDD randomized to receive escitalopram, duloxetine, or CBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 57 publications
1
31
0
Order By: Relevance
“…In brief, meta-analytic studies have shown that combination treatment is more effective than pharmacology alone, psychological treatment alone and the combination of psychological treatment and placebo (Cuijpers et al, 2014b; De Maat et al, 2007; Pampallona et al, 2004). Moreover, a recent trial has shown benefits of both adding psychological treatment to antidepressant medication and adding antidepressant medication to psychological treatment (CBT) in patients who did not achieve remission with either alone (Dunlop et al, 2019). This finding is important clinically because it suggests that the sequence in which the treatments are combined (CBT or antidepressant monotherapy commenced first) does not affect the extent to which the patient can benefit from combining treatments.…”
Section: Treatmentsmentioning
confidence: 99%
“…In brief, meta-analytic studies have shown that combination treatment is more effective than pharmacology alone, psychological treatment alone and the combination of psychological treatment and placebo (Cuijpers et al, 2014b; De Maat et al, 2007; Pampallona et al, 2004). Moreover, a recent trial has shown benefits of both adding psychological treatment to antidepressant medication and adding antidepressant medication to psychological treatment (CBT) in patients who did not achieve remission with either alone (Dunlop et al, 2019). This finding is important clinically because it suggests that the sequence in which the treatments are combined (CBT or antidepressant monotherapy commenced first) does not affect the extent to which the patient can benefit from combining treatments.…”
Section: Treatmentsmentioning
confidence: 99%
“…This research suggest that while switching treatments sometimes improves outcomes, completing two courses of dissimilar treatments does not lead to remission rates close to 100%. For example, in the Emory PREDICT study, the pooled rate of response after adding CBT or antidepressants to a failed course of either was only 48% (Dunlop et al, 2019). In the Sequenced Treatment Alternatives to Relieve Depression (STAR*D) study, remission rates in the first stage involving antidepressants were around 37%.…”
Section: Powermentioning
confidence: 99%
“…Among the psychotherapeutic approaches Cognitive-Behavioral Therapy (CBT) is the most used modality for the treatment of MDD [13,14] and shows a signi cant adjunctive effect to pharmacological treatment, helping in the reduction of depressive symptoms and MDD recurrence [1,15]. However, studies analyzing CBT as monotherapy for the treatment of MDD are less conclusive and its e cacy has been related to MDD severity [16,17].…”
Section: Introductionmentioning
confidence: 99%